A single-step one pot synthesis of O, O′-dialkyl N, N-dialkylphosphoramidates from dialkylphosphites. Issue 33 (17th August 2016) - Purohit, Ajay Kumar; Pardasani, Deepak; Kumar, Ajeet; Goud, D. Raghavender; Jain, Rajiv; Dubey, D.K.
Graphical abstract: Highlights: Condensation of H-phosphonate and sec-amines was carried out at room temperature. CWC relevant dialkyl N, N -dialkylphosphoramidates were synthesized in good yields. Use of inorganic reagents resulted in easy work up and pure product. The reactions are operationally simple to perform. Abstract: An efficient synthetic method has been developed to obtain chemical weapons convention (CWC)-related O, O ′-dialkyl- N, N -dialkylphosphoramidates from dialkylphosphites using inorganic reagents (CuCl2 and Cs2 CO3 ) at room temperature.